Measured extent of agricultural expansion depends on analysis technique. (31st January 2017) - Dunn, Jennifer B.; Merz, Dylan; Copenhaver, Ken L.; Mueller, Steffen
Abstract: Concern is rising that ecologically important, carbon‐rich natural lands in the United States are losing ground to agriculture. We investigate how quantitative assessments of historical land‐use change (LUC) to address this concern differ in their conclusions depending on the data set used through an examination of LUC between 2006 and 2014 in 20 counties in the Prairie Pothole Region using the Cropland Data Layer, a modified Cropland Data Layer dataset, data from the National Agricultural Imagery Program, and in‐person ground‐truthing. The Cropland Data Layer analyses overwhelmingly returned the largest amount of LUC with associated error that limits drawing conclusions from it. Analysis with visual imagery estimated a fraction of this LUC. Clearly, analysis technique drives understanding of the measured extent of LUC; different techniques produce vastly different results that would inform land management policy in strikingly different ways. Best practice guidelines are needed. © 2017 The Authors. Biofuels, Bioproducts and Biorefining published by Society of Chemical Industry and John Wiley & Sons, Ltd.